(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the results of surgical wound care for infection after circumcision treated at the Andrology Center from 2017 to 2021. Subjects and methods: Descriptive study, retrospective follow-up, convenient sampling on 35 patients receiving care for post-circumcision at the Center for Andrology, Viet Duc Friendship Hospital from 2017-2021. Results: The average age of patients was 30.9, the oldest was 70 years old, and the youngest was 9 years old. 45.7% of people change dressings themselves at home. Which, the number of dressing changes more than 1 time accounts for only 14.3%. Patients are mainly circumcised at the district level and in private clinics. There were 32 patients with a rate from satisfied to very satisfied, accounting for 91.4% with nursing care. 3% of patients are not satisfied with the quality of nursing care. Conclusion: Post-circumcision infection is related to the quality of nursing care. The improvement of nursing skills in counseling and post-operative care will limit infections after circumcision.